Misconceptions About Evolution in Biology Among Secondary School Students in Nigeria - Matazu, Suleiman Sa'adu; Isma'il, Akilu (MultiTech Publisher, 2024)
Secondary school students often hold misconceptions about evolutionary concepts due to factors such as religious beliefs, cultural influences, and inadequate educational resources. Finding out these misconceptions is central for cultivating accurate scientific understanding among students. This study employed a mixed methods approach, combining quantitative surveys and qualitative interviews. The main objective was to investigate misconceptions about evolutionary concepts among Senior Secondary Three (SS 3) students from public and private schools in Sabon Gari Local Government Area of Kaduna State, Nigeria. Data were collected using a questionnaire tagged “Misconceptions about Evolutionary Concepts (MEC)” and interview guide. Both MEC and interview guide were validated by experts. The instruments were pilot tested, and the MEC yielded a reliability coefficient of 0.85. Quantitative data from the survey were analyzed using descriptive statistics; mean, standard deviation, and frequency distributions, while qualitative data from the interviews were analyzed using thematic analysis. The findings revealed widespread misconceptions, particularly regarding natural selection, genetic variation, and common ancestry. Religious beliefs and cultural narratives were found to influenced students' understanding of evolution. The study recommended including culturally sensitive content in teaching evolution to respectfully address religious and cultural perspectives while promoting scientific literacy.